SISTEM INFORMASI PASIEN RAWAT INAP DI RUMAH SAKIT ISLAM BANYUBENING BOYOLALI - Happyanto, Merry Kurnia; Anwariningsih, Sri Huning; Wahyu Utami, Yustina Retno (2086-4221, 2013)
Today, Banyubening Hospital still use the manual information system which the data of patients are done by written the file. This method has some weaknesses, such as human error or takes a long time. The purpose of the research is to develop information system inpatient at RSI Banyubening Boyolali. The development system is the processing data of inpatient that is done by human before is changed to be computer based system. The changing is needed in order to make easier processing data and present information well to avoid some weaknesses hat are often found in the system manual processing.